Anisotropic conductive film, method for manufacturing electronic component, and card laminate

By using solder particles and thermoplastic resins of non-eutectic alloys or eutectic alloys in anisotropic conductive films, combined with hot crimping technology and X-ray inspection, the problem of non-destructive observation of the bonding quality of the IC chip and the card components is solved, and high-reliability bonding is achieved.

CN119895668APending Publication Date: 2025-04-25DEXERIALS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380067266.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-11-14
Filing Date
2023-11-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When the IC chip is crimped to the card member, it is impossible to observe whether the melting of the solder particles is good in a non-destructive manner, resulting in difficulty in evaluating the bonding quality.

Method used

Solder particles containing non-eutectic alloys or eutectic alloys and an anisotropic conductive film of thermoplastic resins are used to bond the IC chip to the card member through hot crimping technology, and the melting of the solder particles is observed by non-destructive inspection methods such as X-rays.

Benefits of technology

A non-destructive assessment of bonding quality is achieved, ensuring good melting of solder particles, thereby improving bonding reliability and bending resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895668A_ABST
    Figure CN119895668A_ABST
Patent Text Reader

Abstract

This anisotropic conductive film is a hot melt adhesive sheet (60) containing conductive particles for joining an IC chip (10) and a substrate (30), and contains solder particles, which are non-eutectic alloys or eutectic alloys, and a thermoplastic resin. In the hot melt adhesive sheet (60) containing conductive particles, the area ratio of the solder particles is 8-50%, and the viscosity at the solidus temperature of the solder particles is 1000-100000 Pa * s.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an anisotropic conductive film, a method for manufacturing an electronic component, and a card laminate. Background Art

[0002] As a method for mounting an IC chip on a smart card, there is a method disclosed in Patent Document 1, for example. The method disclosed in Patent Document 1 is to place a hot-melt adhesive sheet containing conductive particles containing solder particles between a card component and an IC chip, and apply heat and pressure to the sheet. By using such heat and pressure, the solder particles contained in the hot-melt adhesive sheet containing conductive particles are melted, and the conductive part on the IC chip side and the conductive part on the card component side are connected by metal bonding.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 6966659 Summary of the invention

[0006] Problems to be solved by the invention

[0007] For example, when a semiconductor element is bonded to a glass substrate using an anisotropic conductive film containing conductive particles, it is possible to observe whether the conductive particles are well connected by observing the bonded portion of the glass substrate with a microscope. However, when an IC chip is crimped to a card member, the bonded portion is sandwiched between the opaque card member and the IC chip and is not exposed, so it is impossible to observe whether the solder particles are well melted from the outside with a microscope.

[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an anisotropic conductive film, a method for producing an electronic component, and a card laminate that can nondestructively observe whether bonding by an anisotropic conductive film containing solder particles is good or not.

[0009] Solutions for solving problems

[0010] In order to solve the above problems and achieve the purpose, the anisotropic conductive film of the present invention contains solder particles which are non-eutectic alloys or eutectic alloys and a thermoplastic resin, wherein the area ratio of the solder particles is 8 to 50%, and the viscosity of the anisotropic conductive film at the solidus temperature of the solder particles is 1000 to 100000 Pa·s.

[0011] In addition, the manufacturing method of the electronic component of the present invention makes an anisotropic conductive film be interposed between an opaque first electronic component and an opaque second electronic component, and the first electronic component and the second electronic component are joined by thermal compression, the anisotropic conductive film contains solder particles which are non-eutectic alloy or eutectic alloy and a thermoplastic resin, the area ratio of the solder particles is 8 to 50%, and the viscosity of the anisotropic conductive film at the solidus temperature of the solder particles is 1000 to 100000 Pa·s.

[0012] Furthermore, in the method for manufacturing the electronic component, the electronic component may also be a dual-interface card.

[0013] Furthermore, in the method for manufacturing an electronic component, the first electronic component may be a biometric sensor.

[0014] In addition, the card stack of the present invention has a first electronic component, a second electronic component, a substrate on which the second electronic component is configured, and an anisotropic conductive film, wherein the anisotropic conductive film contains solder particles which are non-eutectic alloys or eutectic alloys and a thermoplastic resin, the area ratio of the solder particles is 8 to 50%, the viscosity of the anisotropic conductive film at the solidus temperature of the solder particles is 1000 to 100000 Pa·s, and the first electronic component and the second electronic component are joined through the anisotropic conductive film.

[0015] Furthermore, in the card stack, the first electronic component may be a biometric sensor.

[0016] Effects of the Invention

[0017] According to the present invention, whether or not bonding by an anisotropic conductive film containing solder particles is good can be observed in a non-destructive manner. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a top view showing an example of a smart card.

[0019] Figure 2 This is a top view of the back side of the IC chip.

[0020] Figure 3 is a schematic diagram of a cross section of a smart card.

[0021] Figure 4 It is a top view of the IC chip area.

[0022] Figure 5A It is a figure which shows the content of a preparation process.

[0023] Figure 5B It is a figure which shows the content of a preparation process.

[0024] Figure 5C It is a figure which shows the content of a preparation process.

[0025] Fig. 6A It is a figure which shows the content of a joining process.

[0026] Figure 6B It is a figure which shows the content of a joining process.

[0027] Figure 6C It is a figure which shows the content of a joining process.

[0028] Fig. 7A This is an X-ray photograph of the part that was heat-pressed.

[0029] Figure 7B This is an X-ray photograph of the part that was heat-pressed.

[0030] Figure 7C This is an X-ray photograph of the part that was heat-pressed.

[0031] Fig. 8A This is an X-ray photograph of the part that was heat-pressed.

[0032] Figure 8B This is an X-ray photograph of the part that was heat-pressed.

[0033] Figure 8C This is an X-ray photograph of the part that was heat-pressed. DETAILED DESCRIPTION

[0034] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. It should be noted that the present invention is not limited to the embodiments described below. In addition, in the description of the accompanying drawings, the same or corresponding elements are appropriately marked with the same figure numerals. Moreover, the accompanying drawings are schematic, and it should be noted that the dimensional relationship of each element is sometimes different from the actual situation. There may also be parts with different dimensional relationships and ratios between the drawings.

[0035] <1. Smart Card>

[0036] Figure 1It is a top view of a smart card 1 which is an example of an embodiment of the present invention. Smart card 1 is, for example, a dual interface card having two interfaces, contact type and contactless type, in one IC (integrated circuit) chip. Smart card 1 is an example of a card laminate. Smart card 1 is also called an "IC card" or a "chip card". Smart card 1 has an IC chip 10, an antenna 20 for contactless communication and generating electromotive force, and a substrate 30. It should be noted that smart card 1 can also be a hybrid card equipped with a contact IC chip and a contactless IC chip. In addition, smart card 1 can also be a fingerprint authentication card equipped with a fingerprint sensor as an example of a biometric sensor, or a card with a one-time password function assembled with a battery element, a display element, etc. These IC chips, sensors, and elements have pads that are electrically connected to the portion that becomes the electrode on the substrate 30 side.

[0037] The IC chip 10 is a chip having an integrated circuit for recording and calculating information (data), and is an example of a non-transparent first electronic component. The IC chip 10 has a contact with a reader terminal of the smart card 1 on its surface. Figure 2 The back side of the IC chip 10, that is, the side opposite to the side having the contact with the reading terminal, is shown in a top view. The back side of the IC chip 10 has a molded portion 101 for sealing the integrated circuit, and a first electrode portion 102a and a second electrode portion 102b electrically connected to the antenna 20.

[0038] The antenna 20 is a wiring arranged in a spiral shape and is used for communicating with the contactless reading terminal using radio waves. The antenna 20 is an example of a second electronic component. In addition, the antenna 20 generates power by electromagnetic induction from the radio waves emitted by the contactless reading terminal and supplies the generated power to the IC chip 10.

[0039] Figure 3: is a schematic diagram of a cross section of the substrate 30. The substrate 30 is a laminated body having an inlay 33 having an antenna 20; core sheets 32 and 34 laminated on both sides of the inlay 33; and cover layers 31 and 35 constituting the front and back sides of the smart card 1. The inlay 33, the core sheets 32 and 34, and the cover layers 31 and 35 are formed of, for example, a resin material. Examples of the resin material constituting the inlay 33, the core sheets 32 and 34, and the cover layers 31 and 35 include PVC (polyvinyl chloride), PET (polyethylene terephthalate), PET-G, PC (polycarbonate), or recycled materials of these materials, ocean plastics (Ocean Plastic), PLA (polylactic acid) and other biodegradable plastics. The substrate 30 is formed by laminating and integrating the inlay 33, the core sheets 32 and 34, and the cover layers 31 and 35 by heating and pressurizing with or without an adhesive.

[0040] As the adhesive for bonding the inlay 33, core sheets 32, 34 and covering layers 31, 35, various materials such as thermoplastic and thermosetting materials can be used, but materials that have the resistance and heat resistance to withstand the cutting process of the substrate 30 and the heating and pressing process with the IC chip 10 are suitable, and thermosetting adhesives are suitable.

[0041] The antenna 20 is formed on the inlay 33. An IC chip region 40 is formed on the base material 30 by cutting. The IC chip region 40 is a region where the IC chip 10 is to be housed, and a part of the antenna 20 is exposed.

[0042] Figure 4 : is a top view of the IC chip region 40. In the IC chip region 40, the first exposed portion 21a and the second exposed portion 21b, which are part of the pattern of the antenna 20, are exposed. The first exposed portion 21a is electrically connected to the first electrode portion 102a through the hot-melt adhesive sheet 60 containing conductive particles, and the second exposed portion 21b is electrically connected to the second electrode portion 102b through the hot-melt adhesive sheet 60 containing conductive particles. As the wiring of the antenna 20, for example, a copper wire is used. From the viewpoint of ensuring a larger overlapping area between the patterns of the first exposed portion 21a and the second exposed portion 21b and the first electrode portion 102a and the second electrode portion 102b, as shown in FIG. Figure 4 As shown, a serpentine fold pattern is preferred. In the central portion of the IC chip region 40, a receiving region 41 for receiving the mold portion 101 is formed by cutting.

[0043] It should be noted that the inlay 33 preferably has a non-through groove or hole in the IC chip area 40 to be accommodated in the IC chip 10. As a result, the resin of the hot-melt adhesive sheet 60 containing conductive particles will flow into the grooves and holes, which can improve the adhesion with the hot-melt adhesive sheet 60 containing conductive particles. In addition, the shortest length of the opening of these grooves and holes is preferably less than the average particle size of the solder particles. Specifically, the lower limit of the shortest length of the opening of the grooves and holes is preferably more than 20% of the average particle size of the solder particles, more preferably more than 30%, and particularly preferably more than 40%. In addition, the upper limit of the shortest length of the opening of the specific hole is preferably less than 80% of the average particle size of the solder particles, more preferably less than 70%, and particularly preferably less than 60%. As a result, the solder particles are more easily embedded in the grooves and holes, the capture of the solder particles is improved, and an excellent electrical connection with the IC chip 10 can be achieved.

[0044] The hot-melt adhesive sheet 60 containing conductive particles is interposed between the inlay 33 and the IC chip 10, and electrically connects the IC chip 10 to the first exposed portion 12a and the second exposed portion 12b of the antenna 20. The hot-melt adhesive sheet 60 containing conductive particles is, for example, an adhesive sheet containing solder particles as a non-eutectic alloy in the form of conductive particles in an adhesive containing a crystalline polyamide having a carboxyl group. It should be noted that in this specification, "non-eutectic alloy" refers to an alloy that does not have a eutectic point. The hot-melt adhesive sheet 60 containing conductive particles is an example of an anisotropic conductive film (ACF: Anisotropic Conductive Film). It should be noted that the solder particles contained in the hot-melt adhesive sheet 60 containing conductive particles are not limited to solder particles as a non-eutectic alloy, and may also include solder particles as a eutectic alloy.

[0045] The smart card 1 of this embodiment is provided with a hot melt adhesive sheet 60 containing conductive particles, which contains solder particles as a non-eutectic alloy in an adhesive containing a crystalline polyamide having a carboxyl group, so that the wettability of the solder can be improved, and excellent connection reliability and bending resistance can be obtained. This is considered to be a flux effect caused by the carboxyl group present in the crystalline polyamide. As a result, the elastic modulus of the hot melt adhesive sheet 60 containing conductive particles can be prevented from being reduced due to the addition of a flux compound, and excellent bending resistance can be obtained. In addition, the smart card 1 of this embodiment realizes metal bonding by melting the solder particles between the circuit (conducting part) of the IC chip 10 and the circuit (conducting part) of the antenna pattern, so that the swelling and elongation caused by the moisture absorption of the adhesive in the wet heat test can be suppressed, and excellent connection reliability can be obtained. It should be noted that the present technology can also be applied to general anisotropic junctions. In addition, the scope of application of the present technology is also roughly the same for the manufacturing method of the junction.

[0046] <2. Method for manufacturing smart card>

[0047] The manufacturing method of the smart card 1 of this embodiment is a method of placing a hot melt adhesive sheet 60 containing conductive particles between the inlay 33 and the IC chip 10 and pressing them together. Figure 5A to Figure 5C , Figure 6A to Figure 6C , the manufacturing method of the smart card 1 is described. The manufacturing method of the smart card 1 is roughly divided into a preparation process, in which an IC chip 10 laminated with a hot-melt adhesive sheet 60 containing conductive particles is prepared, and a bonding process, in which the IC chip 10 laminated with a hot-melt adhesive sheet 60 containing conductive particles is pressed and bonded to the inlay 33.

[0048] [Preparation process]

[0049] Figure 5A to Figure 5C 1 is a diagram showing the contents of the preparation process. The preparation process includes a sheet punching process, a pasting process, and an IC chip punching process. Figure 5A to Figure 5C The preparation process is described below. In the preparation process, the sheet punching process is first performed. Figure 5A 1 and 2. The figure shows a process of punching out a region corresponding to the shape of the molded portion 101 in the tape-shaped hot-melt adhesive sheet 60 containing conductive particles. The hot-melt adhesive sheet 60 containing conductive particles is supplied in the form of a film package wound around a winding core, for example.

[0050] After the sheet punching process, the pasting process is performed. The pasting process is a process of pasting the hot melt adhesive sheet 60 containing conductive particles to the back of the IC chip 10. In the pasting process, for example, Figure 5B As shown, the hot-melt adhesive sheet 60 containing conductive particles is placed on the IC chip 10 accommodated in the carrier tape 70, and the hot-melt adhesive sheet 60 containing conductive particles is laminated to the connection surface of the IC chip 10 by heating and pressing. Here, the hot-melt adhesive sheet 60 containing conductive particles has been punched out in a shape corresponding to the molded portion 101, so the hot-melt adhesive sheet 60 containing conductive particles is in contact with the first electrode portion 102a and the second electrode portion 102b, and the molded portion 101 is exposed from the punched area. It should be noted that the pasting process can also be a temporary pasting process of pasting the hot-melt adhesive sheet 60 containing conductive particles on the back of the IC chip 10 at a low temperature.

[0051] When the pasting process is a laminating process, a pressurized laminator or a vacuum pressurized laminator can be used. Since the pasting process is a laminating process, a relatively large area can be loaded at one time compared to a temporary pasting process. In addition, when the pasting process is a temporary pasting process, only minimal changes such as setting and changing of tools are required for existing equipment, so economic advantages can be obtained.

[0052] In the pasting process, the temperature reached by the hot-melt adhesive sheet 60 containing conductive particles is preferably higher than the temperature at which the adhesive flows and lower than the temperature at which the solder melts. Here, the temperature at which the adhesive flows may be a temperature at which the melt viscosity of the hot-melt adhesive sheet 60 containing conductive particles reaches 1000 to 100000 Pa·s, preferably a temperature at which the melt viscosity reaches 1000 to 100000 Pa·s. Thus, the hot-melt adhesive sheet 60 containing conductive particles can be pasted on the back of the IC chip 10 while maintaining the shape of the solder particles. It should be noted that the melt viscosity of the hot-melt adhesive sheet 60 containing conductive particles can be measured, for example, using a rotational rheometer (manufactured by TA Instruments) under the conditions of a measuring pressure of 5 g, a temperature range of 30 to 200° C., a heating rate of 10° C. / min, a measuring frequency of 10 Hz, a measuring plate diameter of 8 mm, and a load change of 5 g on the measuring plate.

[0053] After the pasting process, the IC chip punching process is performed. In the IC chip punching process, Figure 5C As shown, the IC chip 10 to which the hot-melt adhesive sheet 60 containing conductive particles is attached is punched out from the carrier tape 70 , and the IC chip 10 is taken out from the carrier tape 70 .

[0054] [Joining process]

[0055] Figure 6A to Figure 6C 1 is a diagram showing the contents of the bonding process. The IC chip 10 taken out from the carrier tape 70 in the preparation process is bonded to the substrate 30 in the bonding process. The bonding process includes a groove forming process, a placement process, and a pressure bonding process. Figure 6A to Figure 6C The bonding process is described below. In the bonding process, a groove process is first performed. In the groove process, the IC chip area 40 is formed, and the receiving area 41 for receiving the molded portion 101 is formed by deep digging. Through this groove process, Fig. 6A As shown, an IC chip region 40 is formed.

[0056] After the slotting process, a placement process is performed. In the placement process, for example, the IC chip 10 is picked up using a tool with an adsorption mechanism, and the IC chip region 40 is aligned with the IC chip 10, such as Figure 6B As shown, the IC chip 10 is mounted on the IC chip region 40 via a hot-melt adhesive sheet 60 containing conductive particles.

[0057] After the placement process, a pressure bonding process is performed. In the pressure bonding process, a pressure bonding device is used to apply heat and pressure to the IC chip 10 and the substrate 30. Figure 6CAs shown, the IC chip 10 and the inlay 33 are thermally pressed. The number of thermal pressing operations in the pressing process can be set according to the connection object, which can be once, but preferably multiple times. In this way, the card can be prevented from being thermally deformed, the adhesive of the hot-melt adhesive sheet 60 containing conductive particles is fully removed, and the first electrode portion 102a is metal-bonded to the first exposed portion 21a, and the second electrode portion 102b is metal-bonded to the second exposed portion 21b by melting of the solder particles.

[0058] In addition, with respect to the hot pressing temperature in the pressing process, it is preferred that the temperature reached by the hot melt adhesive sheet 60 containing conductive particles is above the melting point of the solder particles. Here, the melting point refers to the solidus temperature. That is, with respect to the hot pressing temperature in the pressing process, it is preferred that the temperature reached by the hot melt adhesive sheet 60 containing conductive particles is above the solidus temperature of the solder particles. Here, the solidus is a curve showing the relationship between the temperature (melting point) of the liquid phase in equilibrium with the solid phase and the composition of the solid phase. The specific temperature reached by the hot melt adhesive sheet 60 containing conductive particles is preferably 120 to 160°C, more preferably 120 to 155°C, and further preferably 120 to 150°C. Thus, the thermal shock of the substrate 30 and the IC chip 10 can be suppressed, and the deformation of the substrate 30 can be prevented.

[0059] In the manufacturing method of the smart card 1 of the present embodiment, since the hot-melt adhesive sheet 60 containing conductive particles containing solder particles in the adhesive containing crystalline polyamide having a carboxyl group is used, the wettability of the solder can be improved, and excellent connection reliability can be obtained. In addition, the manufacturing method of the smart card 1 of the present embodiment can metal-bond the conductive portion of the IC chip 10 and the conductive portion of the pattern of the antenna 20 by melting the solder particles, so that the swelling and elongation caused by the moisture absorption of the adhesive in the wet heat test can be suppressed, and excellent connection reliability can be obtained.

[0060] <3. Hot-melt adhesive sheet containing conductive particles>

[0061] The lower limit of the thickness of the hot-melt adhesive sheet 60 containing conductive particles is preferably 10 μm or more, more preferably 20 μm or more, and further preferably 30 μm or more. In addition, the upper limit of the thickness of the hot-melt adhesive sheet 60 containing conductive particles is preferably 100 μm or less, more preferably 80 μm or less, and further preferably 60 μm or less. Thus, it can be suitably used for manufacturing the smart card 1 in which the IC chip 10 is thermally pressed onto the substrate 30.

[0062] The adhesive contains at least a crystalline polyamide having a carboxyl group. It should be noted that the crystalline resin can be confirmed, for example, by observing an endothermic peak during the temperature rise process in a differential scanning calorimetry. The terminal carboxyl concentration of the crystalline polyamide is preferably 0.5 mgKOH / g or more, more preferably 1.0 mgKOH / g or more, and further preferably 2.0 mgKOH / g or more. In addition, the terminal carboxyl concentration of the crystalline polyamide can also be 50 mgKOH / g or less, 30 mgKOH / g or less or 10 mgKOH / g or less. The terminal carboxyl concentration of the crystalline polyamide can be evaluated, for example, according to JIS K 0070-1992 or ISO2114. As a specific example of a commercially available product of a crystalline polyamide having a carboxyl group, for example, "HX2519", "M1276" made by Arkema Co., Ltd., etc. can be cited.

[0063] By including at least a crystalline polyamide having a carboxyl group in the adhesive, the wettability of the solder can be improved, and excellent connection reliability can be obtained. This is believed to be due to the flux effect generated by the carboxyl group present in the crystalline polyamide. As a result, the elastic modulus of the adhesive layer 50 can be prevented from being reduced due to the addition of the flux compound, and excellent bending resistance can be obtained.

[0064] In addition, the adhesive may also contain other components as needed. As other components, crystalline resins, non-crystalline resins, etc. may be appropriately selected according to the purpose. As a crystalline resin, there is no particular limitation as long as it is a resin having a crystalline region, and for example, polyester resins, polyolefin resins, polyurethane resins, etc. may be cited. As a polyester resin, for example, polyethylene terephthalate resins, polybutylene terephthalate resins, etc. may be cited, and as a polyolefin resin, for example, polyethylene resins, polypropylene resins, polybutene resins, etc. may be cited. In addition, as a non-crystalline resin, the same resins as those exemplified in the description of the crystalline resin may be cited. Among these components, from the viewpoint of being able to bond at low temperatures and in a short time, it is preferred that a crystalline polyester resin be included as another component.

[0065] The proportion of the crystalline polyamide having a carboxyl group in the adhesive is preferably 10 to 100 wt %, more preferably 30 to 100 wt %, and further preferably 50 to 100 wt %. This can improve solder wettability and provide excellent connection reliability.

[0066] The solder particles contained in the hot-melt adhesive sheet 60 containing conductive particles are non-eutectic alloys or eutectic alloys. When a non-eutectic alloy is used as the solder particles, it is preferably an alloy containing two or more elements selected from the group consisting of Sn, Bi, Ag, In, Cu, Sb, Pb, and Zn. As solder particles, for example, Sn-Pb system, Pb-Sn-Sb system, Sn-Sb system, Sn-Pb-Bi system, Bi-Sn system, Sn-Bi-Cu system, Sn-Cu system, Sn-Pb-Cu system, Sn-In system, Sn-Ag system, Sn-Pb-Ag system, Pb-Ag system, etc. specified in JIS Z 3282-2017 (corresponding international standard: ISO9453:2014) can be appropriately selected according to the terminal material, connection conditions, etc.

[0067] The lower limit of the solidus temperature (melting point) of the solder particles is preferably above 110°C, more preferably above 130°C, and further preferably above 135°C. The upper limit of the liquidus temperature of the solder particles can be below 210°C, preferably below 200°C, more preferably below 195°C, and further preferably below 190°C. Here, the liquidus is a curve showing the relationship between the temperature (melting point) of the liquid phase in equilibrium with the solid phase and the composition of the liquid phase. In addition, the upper limit of the solidus temperature of the solder particles can be below 155°C, preferably below 150°C, more preferably below 145°C, and further preferably below 140°C. In addition, with respect to the solder particles, it is not a problem for the flux compound to be directly bonded to the surface for the purpose of activating the surface. By activating the surface, metal bonding with metal wires and electrodes can be promoted.

[0068] In addition, the solidus temperature (melting point) of the solder particles is 155°C or less, preferably 150°C or less, and preferably one or more selected from the group consisting of Sn-Bi-Cu alloy, Sn-Bi-Ag alloy, Sn-Bi alloy, Sn-Pb-Bi alloy and Sn-In alloy. Specific examples of solder particles include Sn30Bi0.5Cu, Sn30Bi, Sn40Bi, Sn50Bi, Sn58Bi, Sn40Bi0.1Cu, Sn43Pb14Bi, Sn20In, etc. Thus, excellent connection reliability can be obtained.

[0069] In addition, solder particles can be mixed and dispersed in the resin of the hot melt adhesive sheet 60 containing conductive particles, or can be configured in a separated state. The configuration can be carried out according to a certain rule. As a scheme of regular configuration, lattice arrangements such as square lattices, hexagonal lattices, rhombic lattices, and rectangular lattices can be listed. In addition, solder particles can also be configured as an agglomerate formed by agglomeration of multiple particles. In this case, the configuration of the agglomerate under the top view of the hot melt adhesive sheet 60 containing conductive particles can be a regular configuration or a random configuration in the same manner as the configuration of the above-mentioned solder particles.

[0070] The average particle size of the solder particles is preferably 70% or more, more preferably 80% or more, and even more preferably 95% or more of the thickness of the hot-melt adhesive sheet 60 containing conductive particles. Thus, during thermocompression bonding, the solder particles can be easily sandwiched between the conductive portion of the IC chip 10 and the conductive portion of the substrate 30, and metal bonding can be performed.

[0071] The lower limit of the average particle size of the solder particles is preferably 10 μm or more, more preferably 15 μm or more, and further preferably 20 μm or more. In addition, the upper limit of the average particle size of the solder particles is preferably 50 μm or less, more preferably 45 μm or less, and further preferably 40 μm or less. In addition, the maximum diameter of the solder particles can be set to be less than 200% of the average particle size, preferably less than 150% of the average particle size, and more preferably less than 120% of the average particle size. By having the maximum diameter of the solder particles within the above range, the solder particles can be clamped between the conductive portion of the IC chip 10 and the conductive portion of the substrate 30, and the conductive portions are metal-bonded by melting the solder particles.

[0072] In addition, when the solder particles are agglomerates of a plurality of solder particles, the size of the agglomerates may be made equal to the average particle size of the solder particles described above. The size of the agglomerates can be determined by observation using an electron microscope or an optical microscope.

[0073] Here, the average particle size is the average value of the major axis diameter of the particles measured, for example, at N=20 or more, preferably N=50 or more, and more preferably N=200 or more, in an image observed using an electron microscope such as a metal microscope, an optical microscope, or a scanning electron microscope (SEM). In the case where the particles are spherical, it is the average value of the particle diameter. In addition, it can also be a measured value obtained by measuring the observed image using a known image analysis software ("WinROOF": Mitani Shoji (Strain), "Azokun (registered trademark)": Asahi Kasei Engineering Co., Ltd., etc.), or a measured value (N=1000 or more) obtained by measuring using an image-type particle size distribution measuring device (for example, FPIA-3000 (Malvern Company)). The average particle size obtained from the observed image and the image-type particle size distribution measuring device can be set as the average value of the maximum length of the particles. It should be noted that when preparing the hot-melt adhesive sheet 60 containing conductive particles, the manufacturer's nominal value (Manufacturer value) such as the particle size (D50) at which the frequency accumulation in the particle size distribution obtained by the laser diffraction / scattering method reaches 50% and the arithmetic mean diameter (preferably based on volume) can be simply used.

[0074] The area ratio of the solder particles is preferably 8 to 50%, and more preferably 9.5 to 50%. The area ratio of the solder particles is calculated from the particle size of the solder particles contained in the hot-melt adhesive sheet 60 containing conductive particles before the pasting process. Specifically, the top view image of the hot-melt adhesive sheet 60 containing conductive particles before the pasting process is observed by a microscope, and the area ratio of the solder particles is calculated based on the particle size of the solder particles contained in the hot-melt adhesive sheet 60 containing conductive particles before the pasting process. 2 The particle size of each solder particle contained in each region is measured. Next, the area of ​​each solder particle in the top view is calculated based on the measured particle size, and the total area of ​​the calculated solder particles / 1 mm is used. 2 )×100”. Next, the average of the area ratios of the observed multiple areas is calculated, and the calculated average value is used as the area ratio of the solder particles contained in the hot-melt adhesive sheet 60 containing conductive particles.

[0075] Figure 7A to Figure 7C This is a photograph of the portion that was thermally compressed in the thermal compression step described above. Fig. 7A This is a photograph of a hot-melt adhesive sheet 60 containing conductive particles having a solder particle area ratio of 4.5%, which was subjected to thermocompression bonding at a temperature at which springback occurs. Fig. 7A As shown, when the area ratio of solder particles is less than 8%, springback is difficult to observe in non-destructive inspection by X-rays due to the small number of solder particles, and it is impossible to determine whether the bonding of the solder particles is good or not. Figure 7B and Figure 7C This is a photograph of a hot-melt adhesive sheet 60 containing conductive particles having a solder particle area ratio of 8%, which was subjected to thermocompression bonding at a temperature at which springback occurs. Figure 7B As shown, in the IC chip 10, in the electrode portion (first electrode portion 102a, second electrode portion 102b) electrically connected to the antenna 20 by solder particles, the solder particles will flow away and it is difficult to observe the rebound, but outside the electrode portion, such as Figure 7C As shown, solder particles can be observed. Therefore, the lower limit of the area ratio of solder particles is set to 8%. It should be noted that when the area ratio of solder particles reaches 9.5% or more, melting of solder particles can be visually confirmed and springback can be observed in the electrode portion. Therefore, the area ratio of solder particles is preferably 9.5% or more.

[0076] Regarding the upper limit of the area ratio of solder particles, when the area ratio of solder particles exceeds 50%, the adhesive force between the IC chip 10 and the substrate 30 becomes insufficient due to the decrease in the resin component in the adhesive. In addition, when the hot-melt adhesive sheet 60 containing conductive particles is used to bond the electrode on the substrate 30 side to a component such as a fingerprint sensor where the distance between adjacent electrodes is short, when the area ratio of solder particles exceeds 50%, the solder particles may cause a short circuit between adjacent electrodes. Therefore, the upper limit of the area ratio of solder particles is set to 50%.

[0077] In addition, regarding the viscosity of the hot-melt adhesive sheet 60 containing conductive particles, it is preferable that the viscosity at the solidus temperature of the solder particles is 1000 to 100000 Pa·s. When the viscosity is less than 1000 Pa·s, bubbles are generated in the hot-melt adhesive sheet 60 containing conductive particles during thermocompression bonding, causing rebound and poor bonding. In addition, when the viscosity exceeds 100000 Pa·s, the resin in the adhesive and the solder particles do not flow sufficiently, resulting in poor bonding.

[0078] [Other additives]

[0079] In addition to the above-mentioned adhesive and solder particles, various additives can also be added to the hot-melt adhesive sheet 60 containing conductive particles within the scope of not damaging the effect of the present invention. For example, in order to improve the gas barrier property and elastic modulus, nano-sized (primary particle size is more than 1nm and less than 1000nm) silicon dioxide can be dispersed. In addition, in order to control the height of the solder particles after crimping within a certain range, resin particles, rubber particles, silicone rubber particles, silicon dioxide, etc. of a specified size can also be dispersed as spacer particles. In addition, within the scope of not damaging the effect of this technology, thermosetting resins and curing agents can also be added.

[0080] Example

[0081] In this embodiment, a hot-melt adhesive sheet 60 containing conductive particles containing solder particles was prepared, and a smart card 1 was prepared using the hot-melt adhesive sheet 60. Then, the adhesive force between the IC chip 10 and the substrate 30 was evaluated, and whether the bonding between the IC chip 10 and the substrate 30 was good was evaluated by non-destructive inspection. It should be noted that this embodiment is not limited to these contents.

[0082] [Production of solder particles]

[0083] Metal materials were placed in a heated container according to a predetermined mixing ratio, melted, and then cooled to obtain a solder alloy. The solder alloy was powdered by atomization and classified to a particle size range of 20 to 38 μm to obtain solder particles with the following composition.

[0084] Type 4 Sn-40Bi (non-eutectic, solidus temperature: 139°C, liquidus temperature: 167°C).

[0085] Type 4 Sn-58Bi (eutectic, solidus temperature and liquidus temperature: 138°C).

[0086] [Production of hot-melt adhesive sheet containing conductive particles]

[0087] The following resins and fillers were prepared.

[0088] PES-111EE (manufactured by Toagosei Co., Ltd., crystalline polyester) was dissolved at a solid content / cyclohexanone ratio of 25 / 75.

[0089] HX2519 (manufactured by Arkema Co., Ltd., crystalline polyamide having a carboxyl group, terminal carboxyl group concentration of 6.56 mgKOH / g).

[0090] B-30 (manufactured by Sakai Industry Co., Ltd., barium sulfate), particle size: 0.3 μm.

[0091] As shown in Table 1, the above resins were mixed and stirred in a predetermined amount (parts by mass) according to the solid content to obtain a mixed varnish. Then, solder particles were added to the obtained mixed varnish to obtain a resin composition containing conductive particles. The obtained resin composition containing conductive particles was coated on a 50 μm thick PET film to an average thickness of 40 μm after drying, dried at 70° C. for 5 minutes, and then dried at 120° C. for 5 minutes to prepare a hot melt adhesive sheet 60 containing conductive particles.

[0092] [Smart Card Production]

[0093] As a component of the smart card 1, a substrate 30 is prepared, which is a laminated body formed by stacking a cover layer 31, a core sheet 32, an inlay 33 having an antenna 20, a core sheet 34, and a cover layer 35. In the IC chip area 40 of the substrate 30, a copper wire with a diameter of 100 μm is exposed from the PVC serving as the substrate 30. In addition, a chip module (10.6 mm×8.0 mm, gold-plated) is prepared as a test chip 10. The thickness of the chip module is approximately 235 μm, and the thickness of the electrode portion connected to the antenna 20 is less than 35 μm. It is a nickel / gold-plated copper 6-pin module.

[0094] The hot-melt adhesive sheet 60 containing conductive particles was laminated on the back of the IC chip 10. Then, the IC chip 10 to which the hot-melt adhesive sheet 60 containing conductive particles was attached was placed on the IC chip region 40, and a smart card 1 was produced by performing four times of thermocompression bonding under the first conditions of 195° C., 2.5 bar, and 0.7 seconds, and a smart card 1 was produced by performing four times of thermocompression bonding under the second conditions of 220° C., 2.5 bar, and 0.7 seconds.

[0095] [Evaluation of the joint]

[0096] Regarding whether the melting of the solder particles is good, the IC chip region 40 is observed by an X-ray inspection machine, and whether the bonding is good or not is determined based on the melting state of the solder particles. Figure 8A to Figure 8C This is a photo of the part that was heat-pressed in the heat-pressing step described above. Figure 8A to Figure 8C In the figure, solder particles Pa are represented by black dots. Fig. 8A In the figure, the shape of the solder particle Pa is circular, and melting of the solder particle is not observed. Figure 8C In the figure, as can be seen in the area SB indicated by the dotted line, a plurality of molten solder particles Pa are melted along the bubbles generated by the springback and arranged in a circular shape, showing a state in which there are springback traces in the melting process of the solder particles Pa. Figure 8B In the evaluation of the joint, the following cases were judged as "OK", and the others were judged as "NG". This was the case when the thermocompression bonding was performed under the first condition described above. Figure 8B As shown in FIG. 1 , melting of solder particles can be observed. When thermal compression bonding is performed under the second condition described above, as shown in FIG. Figure 8C As shown, the rebound marks can be seen.

[0097] [Evaluation of Adhesion Strength]

[0098] Regarding the adhesion between the IC chip 10 and the inlay 33, the force required to push the IC chip 10 out of the substrate 30 was measured by applying force to the back side of the IC chip 10 according to the TM-423 test specified in CQM (Card Quality Management), which is a standard of MasterCard (registered trademark). Specifically, a hole was opened from the back side of the substrate 30 toward the IC chip region 40, and a probe with a diameter of 5 mm was inserted into the hole, and force was applied to the back side of the IC chip 10 at a speed of 30 mm / min. If the force applied by the probe to release the IC chip 10 from the inlay 33 was less than 100 N, it was judged as "NG", and if it was more than 100 N, it was judged as "OK".

[0099] Table 1 shows the evaluation results of the blending, joining, and adhesive strength of the hot-melt adhesive sheets 60 containing conductive particles in the first to fourth examples and the first to third comparative examples.

[0100] [Table 1]

[0101]

[0102] In the first comparative example in which the area ratio of the solder particles was 7.0%, no rebound was observed in the evaluation of the bonding. In the second comparative example in which the area ratio of the solder particles was 55%, in the evaluation of the bonding strength, since the force when the probe detached the IC chip 10 from the inlay 33 was less than 100N, excellent bonding strength could not be obtained. This is believed to be due to the low adhesive strength caused by the small amount of resin component. In the third comparative example in which the resin viscosity was 105000Pa·s, due to the high viscosity of the resin, the solder particles and the resin could not flow sufficiently, and it became "NG" in both the evaluation of the bonding and the evaluation of the bonding strength.

[0103] On the other hand, in the first to fourth examples, where the area ratio of solder particles was in the range of 8 to 50% and the viscosity was in the range of 1000 to 100000 Pa·s, the melting of solder particles was observed under the first condition, the trace of springback was observed under the second condition, and excellent results were obtained for the adhesive force. In the first example, the resin also flowed under the first condition, and the melting of solder particles was also confirmed. Under the second condition, due to the sufficient particle density, the solder particles were circled to show the bubble area. In addition, in the first example, the adhesive force exceeded 100N under both the first and second conditions. Although the second example used eutectic solder as solder particles, it was good in the evaluation of bonding and the evaluation of adhesive force as in the first example. In the third example, the area ratio of non-eutectic solder particles was increased to 50%, but it was good in the evaluation of bonding and the evaluation of adhesive force as in the first example. In the fourth example, barium sulfate was added to the third example to adjust the viscosity to 90,000 Pa·s. However, similarly to the first example, both the bonding evaluation and the adhesive strength evaluation were good.

[0104] Description of Reference Numerals

[0105] 1: smart card; 10: IC chip; 20: antenna; 21a: first exposed portion; 21b: second exposed portion; 30: substrate; 60: hot-melt adhesive sheet containing conductive particles; 102a: first electrode portion; 102b: second electrode portion.

Claims

1. An anisotropic conductive film, wherein: The anisotropic conductive film contains solder particles which are non-eutectic alloy or eutectic alloy and a thermoplastic resin. The area ratio of the solder particles is 8 to 50%. The viscosity of the anisotropic conductive film at the solidus temperature of the solder particles is 1000 to 100000 Pa·s.

2. A method for manufacturing an electronic component, wherein: An anisotropic conductive film is interposed between an opaque first electronic component and an opaque second electronic component, and the first electronic component and the second electronic component are bonded by thermocompression bonding. The anisotropic conductive film contains solder particles which are non-eutectic alloy or eutectic alloy and a thermoplastic resin. The area ratio of the solder particles is 8 to 50%. The viscosity of the anisotropic conductive film at the solidus temperature of the solder particles is 1000 to 100000 Pa·s.

3. The method for manufacturing an electronic component according to claim 2, wherein: The electronic component is a dual-interface card.

4. The method for manufacturing an electronic component according to claim 2, wherein: The first electronic component is a biometric sensor.

5. A card stack, wherein: The card stack includes a first electronic component, a second electronic component, a substrate on which the second electronic component is disposed, and an anisotropic conductive film. The anisotropic conductive film contains solder particles that are non-eutectic alloy or eutectic alloy and a thermoplastic resin, the area ratio of the solder particles is 8 to 50%, and the viscosity of the anisotropic conductive film at the solidus temperature of the solder particles is 1000 to 100000 Pa·s. The first electronic component and the second electronic component are bonded to each other through the anisotropic conductive film.

6. The card stack according to claim 5, wherein: The first electronic component is a biometric sensor.